2020
DOI: 10.1016/j.ebiom.2020.103034
|View full text |Cite
|
Sign up to set email alerts
|

Canonical WNT pathway is activated in the airway epithelium in chronic obstructive pulmonary disease

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a devastating lung disease, mainly due to cigarette smoking, which represents the third cause of mortality worldwide. The mechanisms driving its epithelial salient features remain largely elusive. We aimed to evaluate the activation and the role of the canonical, β-catenin-dependant WNT pathway in the airway epithelium from COPD patients. Methods The WNT/β-catenin pathway was first assessed by WNT-targeted RNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 66 publications
3
46
0
Order By: Relevance
“…EMT programming is regulated by an intricate network of pathways, including Wingless/Integrase-1 (WNT) and transforming growth factor (TGF)-β ( Lamouille et al, 2014 ). In the last decade, several studies showed that EMT is present in airway tissues from smokers and is further enhanced in COPD patients, both in small ( Milara et al, 2013 ; Mahmood et al, 2015 ) and large airways ( Sohal et al, 2010 , 2011 ; Mahmood et al, 2015 ; Carlier et al, 2020 ). Thus, Sohal and colleagues observed increased expression of EMT-related S100A4 and matrix metalloproteinase (MMP)-9 in the large airways from COPD patients as compared with non-COPD smokers and non-smokers ( Sohal et al, 2010 , 2011 ).…”
Section: Epithelial Alterations In Chronic Respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT programming is regulated by an intricate network of pathways, including Wingless/Integrase-1 (WNT) and transforming growth factor (TGF)-β ( Lamouille et al, 2014 ). In the last decade, several studies showed that EMT is present in airway tissues from smokers and is further enhanced in COPD patients, both in small ( Milara et al, 2013 ; Mahmood et al, 2015 ) and large airways ( Sohal et al, 2010 , 2011 ; Mahmood et al, 2015 ; Carlier et al, 2020 ). Thus, Sohal and colleagues observed increased expression of EMT-related S100A4 and matrix metalloproteinase (MMP)-9 in the large airways from COPD patients as compared with non-COPD smokers and non-smokers ( Sohal et al, 2010 , 2011 ).…”
Section: Epithelial Alterations In Chronic Respiratory Diseasesmentioning
confidence: 99%
“…Interestingly, the dysregulation of these genes and pathways appears usually aggravated in COPD as compared with non-COPD smokers. Finally, our team recently showed that WNT/β-catenin signaling pathway is activated in the large airways of COPD patients, therefore contributing to enhance EMT, as in vitro extrinsic activation of WNT resulted in increased vimentin expression, fibronectin release, and p-SMAD2/TGF-β signaling ( Carlier et al, 2020 ). EMT, associated with CS-induced TGF-β production, could therefore promote airway fibrosis, impaired epithelial repair, as well as carcinogenesis and metastasis potential ( Bartis et al, 2014 ; Sohal, 2015 ; Jolly et al, 2018 ).…”
Section: Epithelial Alterations In Chronic Respiratory Diseasesmentioning
confidence: 99%
“…Interestingly, TGF-β1 pathways are also suggested to play a crucial role in the development of myofibroblasts from tissue fibroblasts through activation of the SMAD pathway [ 26 , 31 ], so although we believe EMT to be a key mechanism in COPD pathogenesis [ 32 ], it is unlikely to be the only growth factor driven mechanism operating throughout the whole thickness of the SA wall [ 33 ]. In addition to the TGF-β1 pathway, we and others have previously shown that the transcription factor clusters of β-catenin/Snail1/Twist is upregulated and with nuclear translocation in smokers and COPD, and their expression is closely related to both EMT activity and lung function [ 28 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Progenitor basal cells are prime candidate to retain epithelial memory in the airways, as do epithelial progenitors in the skin towards mechanical stress (54) or in the gut towards dietary components (55). Interestingly, it was recently shown that WNT signalling that is involved in the later form of epithelial memory and may regulate stemness and tumorigenicity, is upregulated in the COPD AE (47). In line with the recent hypothesis that basal cells serve as repositories of allergic inflammatory memory in respiratory epithelial cells (31), one could propose that airway basal cells also store the memory of repeated injuries by previous exposures to toxics.…”
Section: Discussionmentioning
confidence: 99%